Prevalence and Risk Factors of Intestinal Parasitic Infections among Schoolchildren in Katsina Metropolis, Katsina State, Nigeria - Isma’l, I.; Ahmed, Abdulhamid; Abdullahi, K.; Yusuf, Aliyu Musa; Yar’adua, Zainab A.; Gidado, S. M. (Sahel Journal of Life Sciences FUDMA, 2024)
Intestinal Parasitic Infections (IPIs) are significant causes of morbidity, particularly among school-aged children. This cross-sectional study was conducted to assess the prevalence and risk factors of intestinal parasitic infections among schoolchildren in Katsina Metropolis, Katsina State, Nigeria. A total of 420 schoolchildren from five randomly selected primary schools were enrolled for the study. Socio-demographic data were collected using structured questionnaires administered to both the children and their parents. Stool samples were analyzed using the Kato-Katz and direct wet-mount techniques to identify the presence of parasitic infections. The overall prevalence of intestinal parasitic infections was found to be 33.6%. The most prevalent parasite was Ascaris lumbricoides, detected in 28.0% of the children, and followed by Giardia lamblia (23.3%), Hookworm (22.8%), Entamoeba coli (19.5%), and Trichuris trichiura (6.6%). The prevalence was higher in males (37.1%) compared to females (30.1%). Children aged 6-9 years showed a significantly higher prevalence (38.0%) than those aged ≥10 years (30.0%) (P<0.05). The key risk factors identified included family size, dietary habits, lack of toilet facilities, drinking water sources and the educational status of parents. The study indicates that STHs and intestinal protozoa infections remain prevalent among schoolchildren in Katsina Metropolis, posing a substantial public health challenge. Addressing this issue requires increased public awareness, improved sanitation in schools, and the implementation of school-based deworming programs.